C1q/TNF-related Protein 4 Induces Signal Transducer and Activator of Transcription 3 Pathway and Modulates Food Intake. (1st March 2020) - Li, Yuejie; Ye, Liu; Jia, Gongwei; Chen, Hong; Yu, Lehua; Wu, Dandong
Highlights: Hypothalamic CTRP4 overexpression decreases food intake in vivo . Hypothalamic CTRP4 induces STAT3 signaling and regulates neuropeptides. CTRP4-induced STAT3 signaling seems to be SOCS3-dependent. Abstract: C1q/TNF-related protein 4 (CTRP4) has been reported to decrease food intake and regulate energy homeostasis. However, its underlying mechanism and signaling pathway remain unknown. Using an adenovirus-mediated hypothalamic CTRP4 overexpression model, we investigated the impact of CTRP4 on food intake and signal transducer and activator of transcription 3 (STAT3) signaling pathway in normal chow-fed mice. Expressions of neuropeptides including proopiomelanocortin (POMC) and neuropeptide Y (NPY) were studied in hypothalamus by Western blot and immunochemistry. STAT3 and suppressor of cytokine signaling 3 (SOCS3) were determined by Western blot. STAT3 signaling pathway was also investigated in Neuro 2A (N2a) cells after CTRP4 overexpression intervention. We found that food intake decreased significantly in mice under normal chow condition after CTRP4 overexpression. Both immunohistochemistry and Western blot demonstrated that POMC expression was significantly increased while NPY expression was significantly decreased. The changes of neuropeptides were accompanied by significant increased STAT3 phosphorylation and decreased SOCS3 levels. The same changes of neuropeptides and STAT3 signaling were also found in N2a cells after CTRP4 overexpression intervention. Collectively, our data reveals that CTRP4 induces the activation of STAT3 signaling and decreases food intake.